PENGEMBANGAN MODEL PEMBELAJARAN LOMPAT JAUH GAYA JONGKOK DENGAN PENDEKATAN PERMAINAN HALRING PADA SISWA SEKOLAH DASAR (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to produce a model for the development of learning long jump squat style approach halring game in the fourth grade students of SD Negeri 01 Gununglangit District of Kalibening , Banjarnegara regency.This study is a research method development . The procedures include requirements analysis of product development , product manufacture beginning , the first product revision , field trials , the revised final results , product testing , design testing , expert evaluation , small group testing , the first product revision , field trials , test subjects try , data types and data collection instruments . The data was collected using field observation and questionnaires were obtained from expert evaluation and the results of the questionnaire by the students . The data analysis technique used is descriptive percentages .The results obtained by learning experts average percentage analysis results of 95.33 % with a product very well . The results of the student questionnaire data on a small test group gained an average of 88.05 percentage answer with , % with category B. And questionnaire data from a large group of students test answers obtained with the percentage 84.50 % with category B. Based on the research data , it was concluded that the game Halring effectively and in accordance with the characteristics of students that can be used in learning Penjasorkes .